Clinical manifestations, diagnosis, and surgical treatment of compressive common peroneal neuropathy at the level of the fibular head - M. G. Bashlachev; G. Yu. Evzikov; V. A. Parfenov (Неврология, нейропсихиатрия, психосоматика, 2021)
Common peroneal neuropathy (CPN) is the most common tunnel neuropathy in the lower extremities, many issues of diagnosis and treatment of which require further study.Objective: to analyze the clinical manifestations of CPN, methods of its diagnosis and treatment results.Patients and methods. Eighty patients (31 women and 49 men) aged 18 to 82 years (mean age, 51 years) with compressive CPN were followed up during 2012–2018. Unilateral CPN and bilateral CPN were found in 76 and 4 patients, respectively. Eighty-four common peroneal nerve decompression operations were performed.Results and discussion. There was paralytic CPN in 73 (87%) surgical cases, painful CPN in 8 (9.5%), and intermittent CPN in 3 (3.5%). Diagnostic errors (when CPN was regarded as discogenic radiculopathy or lumbar stenosis) were noted in the painful and intermittent forms of the disease. After surgical treatment, complete recovery of peroneal nerve function was observed in 61 (72.6%) of the 84 surgical cases; its partial recovery in 15 (17.9%). Positive results were seen in all cases of painful and intermittent CPN, whereas they were more often observed in paralytic CPN if the operation was performed early (up to 12 months) after the onset of the disease.Conclusion. Common peroneal nerve decompression is an effective and safe therapeutic method that, in painful and intermittent CPN, leads to complete reversal of symptoms and, in the paralytic form of the disease, it is most effective in the early stages of the disease.